Management and cost accounting : Supplement,. Professional exam questions from past ACCA, ICAI and CIMA papers with selected answers - Malik,.Kamran; Horngren, Charles T.,-.Management and cost accounting (Harlow ; Munich : Financial Times/Prentice Hall, 2005)
This booklet contains 40 questions taken from past CIMA, ACCA, and ICAN exam papers to help students test and consolidate their knowledge and understanding .
oif 17/09/2019
Loans
Keywords: Cost accounting; Managerial accounting; Europe